Pengaruh Kualitas Pelayanan dan Kualitas Produk Terhadap Keputusan Pembelian (Studi Kasus Pada Cafe Ruang Singgah Malang) - Abdun Zaki; Muhammad Ridwan Basalamah; Budi Wahono (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract The purpose of this study was to determine and analyze the influence of Service Quality and Product Quality on Purchasing Decisions (Study at the Singgah Room Café in Malang). The approach used in this study is an associative approach. The population in this study were Consumers of the Malang City Shelter Café. A total of 100 people while the sample in this study used Nonprobability Sampling/Sampling saturation, namely all populations were used as a sample of 100 Consumers of the Malang Singgah Room Café. Data collection techniques in this study used interview techniques, documentation studies, observations, and questionnaires. Data analysis techniques in this study used Multiple Linear Regression Tests, Hypothesis Tests (T Test and F Test), and the Coefficient of Determination. The results of this study prove that the direct influence of service quality affects purchasing decisions and product quality does not affect purchasing decisions (study at the Singgah Room Café in Malang). Keywords: Service Quality, Product Quality, Purchasing Decisions